A Multifunctional Blue‐Emitting Material Designed via Tuning Distribution of Hybridized Excited‐State for High‐Performance Blue and Host‐Sensitized OLEDs. (9th July 2020) - Zhang, Han; Zhang, Bing; Zhang, Yiwen; Xu, Zeng; Wu, Haozhong; Yin, Ping‐An; Wang, Zhiming; Zhao, Zujin; Ma, Dongge; Tang, Ben Zhong
Abstract: Actualizing full singlet exciton yield via a reverse intersystem crossing from the high‐lying triplet state to singlet state, namely, "hot exciton" mechanism, holds great potential for high‐performance fluorescent organic light‐emitting diodes (OLEDs). However, incorporating comprehensive insights into the mechanism and effective molecular design strategies still remains challenging. Herein, three blue emitters (CNNPI, 2TriPE‐CNNPI, and 2CzPh‐CNNPI) with a distinct local excited (LE) state and charge‐transfer (CT) state distributions in excited states are designed and synthesized. They show prominent hybridized local and charge‐transfer (HLCT) states and aggregation‐induced emission enhancement properties. The "hot exciton" mechanism based on these emitters reveals that a balanced LE/CT distribution can simultaneously boost photoluminescence efficiency and exciton utilization. In particular, a nearly 100% exciton utilization is achieved in the electroluminescence (EL) process of 2CzPh‐CNNPI. Moreover, employing 2CzPh‐CNNPI as the emitter, emissive dopant, and sensitizing host, respectively, the EL performances of the corresponding nondoped pure‐blue, doped deep‐blue, and HLCT‐sensitized fluorescent OLEDs are among the most efficient OLEDs with a "hot exciton" mechanism to date. These results could shed light on the design principles for "hot exciton" materials and inspire the development of next‐generation high‐performance OLEDs. Abstract : Full exciton utilization is achieved in the electroluminescence process of 2CzPh‐CNNPI, owing to the balanced distribution of locally excited and charge‐transfer states. Further, this molecule is the first "hot exciton" material that can be employed as the emitter, emissive dopant, and sensitizing host, respectively, and simultaneously achieve high performance in the corresponding blue and host‐sensitized fluorescent organic light‐emitting diodes.